Implementing Sustainability in the Curriculum of Universities Approaches, Methods and Projects (World Sustainability Series, 2018)
This book presents sustainable development themes across universities and introduces methodological approaches and projects to the teaching staff. It has been prepared against this background, to identify ways to better teach about sustainability issues in a university context. It contains a set of papers presented at a Symposium with the same title, held at Manchester Metropolitan University (UK) in March 2017. The event was attended by a number of institutions of higher education active in this field. It involved researchers in the field of sustainable development in the widest sense, from business and economics, to arts and fashion, administration, environment, languages and media studies. Sustainability is seldom systematically embedded in the curriculum at higher education institutions. Yet, proper provisions for curricular integration of sustainability issues as part of teaching programmes across universities are an important element towards curriculum greening. The aims of this book are: (i) to provide teaching staff at universities active and/or interested in teaching sustainable development themes with an opportunity to document and disseminate their works (i.e. curriculum innovation, empirical work, activities, case studies practical projects); (ii) to promote information, ideas and experiences acquired in the execution of teaching courses, especially successful initiatives and good practice; (iii) to introduce methodological approaches and projects which aim to offer a better understanding of how matters related to sustainable development can be tackled in university teaching. Last but not least, a further aim of this book, prepared by the Inter-University Sustainable Development Research Programme (IUSDRP) and the World Sustainable Development Research and Transfer Centre (WSD-RTC), is to catalyse a debate on the need to promote sustainable development teaching today.